POTENSI EKONOMI DALAM ZAKAT DAN WAKAF SAHAM DI INDONESIA - Shulhan Zainul Afkar (istinbath, 2020)
Indonesia, with the largest Muslim population in the world, has great potential for the collection of Islamic social finance. The practice of Zakat and stock Waqf in Indonesia can be classified as new. However, an increase in the activity of the Islamic Capital Market in Indonesia may indicate that the potential for zakat and stock waqf is very large. This research aims to see the economic potential in zakat and stock waqf. this study used a descriptive qualitative method with the type of research library research. the research results reveal that the practice of zakat and stock waqf is permissible, so the economic potential of collecting zakat and stock waqf is very large. PUSKAS BAZNAZ, using the Company’s Stock Waqf Indicator, explained that the potential for share zakat reached Rp 99.7 trillion in 2019. Meanwhile, the potential for waqf itself is based on the assumption that 50% of investors with waqf of Rp 100.000 every month will generate a potential stock waqf of Rp 3.9 billion per month.